New microfocus bremsstrahlung source based on betatron B-18 for high-resolution radiography and tomography; IOP Conference Series: Materials Science and Engineering; Vol. 289 : Modern Technologies for Non-Destructive Testing - Rychkov M. M. Maksim Mikhailovich; Kaplin V. V. Valery Viktorovich; Malikov E. L. Evgeny Lvovich (L'vovich); Smolyanskiy V. A. Vladimir Aleksandrovich; Stepanov I. B. Igor Borisovich; Lutsenko A. S. Artem Sergeevich; Gentselman V. Valentin; Vaskovsky I. K. Ivan Kirillovich (2018, 2018)
Title screen